Changes in Serum Lipids and Lipoproteins Following the Administration of Triton WR-1339 to Splenectomized Rabbits - ASAI, Kanichi; KUZUYA, Masafumi; NAITO, Michitaka; FUNAKI, Chiaki; HAYASHI, Toshio; KUZUYA, Fumio (Dōmyaku kōka = The Journal of Japan Atherosclerosis Society, 1988)
Changes in lipids in whole serum and serum lipoproteins were determined after a single injection of Triton WR-1339 into both splenectomized rabbits and control rabbits. 14 white Japanese male rabbits were divided into two groups: a splenectomy group (Spx group n=8), and a control group (Sham group n=6). After the operation, Triton WR-1339 at a dose of 200mg/kg body weight was administered to the rabbits. Lipids in whole serum and lipoproteins were measured at 0, 6, 24, 48, 72, and 120hr after injection.Triton-induced hyperlipidemia occurred in both groups. However, we found significantly lower levels of serum triglyceride (TG) and TG in very low density lipoprotein (VLDL) at 6 hours after injection in the Spx group and also found no increase in TG to total cholesterol (TC) ratio in VLDL. These data suggest that an inhibitory effect of Triton on lipoprotein lipase activity was partially suppressed from 0 to 6hr in the Spx group.The lipids in low density lipoprotein (LDL) fraction of the Spx group were higher than those of the Sham group at 120hr. This may indicate retarded LDL catabolism in the Spx group and may provide us with a possible explanation for our previous observation: more enhanced dietinduced hyperlipidemia in splenectomized rabbits.